New Technological Knowledge Integration in Industries with Long-Wave Innovation: Case Study of Iran Mining and Mineral Industry - akbar Mohammadi; Nima Garosi Mokhtarzade; Ahmad Jafar nejad (مدیریت صنعتی)
Objective Given the escalating complexity of various scientific fields and the competitive nature of markets, the focus on innovation has become crucial for the survival of businesses in the industry. Industries characterized by rapid new product development often undergo shorter cycles of innovation. Mining and mineral enterprises, recognized as long-wave innovators, must not only assimilate new knowledge and technologies but also effectively incorporate them within their organizational processes. The primary aim of this research is to propose a framework aimed at enhancing the technological capabilities of enterprises with long-wave innovation through the integration of novel technological insights.